ISOMETRIC HANDGRIP EXERCISE UNTUK MENGONTROL TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Mursudarinah; Gita Sandy Patonengan; Rita Dewi Sunarno (Universitas Duta Bangsa Surakarta, 2021)
Introduction: The elderly are one of the vulnerable populations so they are easy to experience various risks of cardiovascular disorders such as hypertension. Hypertension is a non-communicable disease that mostly affects the elderly in various countries. Hypertension is known as a silent killer because this disease can cause death without causing any symptoms. Objectives: To make an overview of isometric handgrip exercise which is one of the nursing interventions to control blood pressure in the elderly with hypertension. Methods: This report is a literature review, in which there are 10 articles taken from a computer database through ResearchGate, PubMed, PubMed, Elsevier, Semantic Scholar. Result: isometric handgrip exercise has an effect in lowering blood pressure in the elderly with hypertension. Conclusion: isometric handgrip exercise has an effect in lowering blood pressure in the elderly with hypertension